IParasitology: Mining the Internet to Test Parasitological Hypotheses. Issue 4 (April 2021) - Poulin, Robert; Bennett, Jerusha; Filion, Antoine; Bhattarai, Upendra Raj; Chai, Xuhong; de Angeli Dutra, Daniela; Donlon, Erica; Doherty, Jean-François; Jorge, Fátima; Milotic, Marin; Park, Eunji; Sabadel, Amandine; et al.
Abstract : Digital data (internet queries, page views, social media posts, images) are accumulating online at increasing rates. Tools for compiling these data and extracting their metadata are now readily available. We highlight the possibilities and limitations of internet data to reveal patterns in host–parasite interactions and encourage parasitologists to embrace iParasitology.